A customer satisfaction-based optimization model for the charging and discharging path and battery swapping stations’ site selection of electric vehicles - Zhang, Yuhong; He, Puyu; Ren, Wenshi; Jiao, Jie; Long, Zhuhan; Jian, Yaling (Frontiers in Energy Research, 2024)
This paper studies the problem of considering customer satisfaction in the no-battery-swap mode and in the power-swap mode. First, with the goal of maximizing customer satisfaction, the total cost of, charging and discharging and the minimum construction cost of swapping stations, the customer time window and the load constraints of electric vehicles are considered. A model of electric vehicle charging and discharging route optimization and replacement station location without battery swapping behavior considering customer satisfaction is established, and then a two-stage improved ant colony-genetic algorithm is designed to solve the model, and finally the comparative analysis considers customer satisfaction. Based on the path optimization results and location decisions considering the cost of charging and discharging, the following conclusions are obtained: (1) Electric vehicle route optimization and swap station location planning considering customer satisfaction can not only effectively reduce logistics distribution costs and replacement costs, but also improve customer satisfaction levels. (2) Reducing the number of route crossings in the process of logistics distribution routes can save electricity costs for electric vehicles and logistics distribution costs, and help reduce the total cost of the entire logistics distribution network. (3) The gradient setting of the electricity price for electricity exchange will reduce the cost of electricity exchange, improve the utilization efficiency of the battery, reduce the cost of logistics and distribution, and improve the electricity exchange revenue of the electricity exchange station.